EFL STUDENTS’ RESPONSES ON TECHNOLOGY-MEDIATED TASK-BASED LANGUAGE TEACHING IN SPEAKING CLASSROOM: A NARRATIVE INQUIRY - Hilda Yulia Nurfadhilah; Indah Purnama Dewi; Evi Karlina Ambarwati (IKIP Siliwangi, 2023)
The purpose of this study was to explore EFL students responses on Technology-Mediated Task-Based Language Teaching where English Foreign language students must complete the speaking instruction task to know whether EFL students had positive or negative response on technology-mediated TBLT in speaking classroom. A total of 5 senior high school students participated in this study and were assigned to create a video production in English using their cellphone camera about procedure text topics assigned by teacher. This study was using qualitative research with narrative inquiry, this research narrate trough oral and written, which are semi-structured interview as an oral narrative and students’ narrative frame as a form of written narrative. The finding showed that four out of five students had positive responses on technology-mediated TBLT in speaking classroom. It proven by the develop of students’ motivation or self-confidence on speaking and the number pf students’ vocabulary size. However, there was a student that response it negatively where the semi-structured interview showed that technology-mediated TBLT was inconvenient for her in speaking classroom, because of the external problem that she faced with the cellphone. Therefore, it can be said that the result of this study is EFL students had positive responses on technology-mediated TBLT in speaking classroom. Keywords: Task-Based Language Teaching; Technology-Mediated Task-Based Language Teaching; Speaking Classroom